(untitled) (Bangladesh Journal of Medical Science, 2020)
Vitriolage is an extreme form of violence in Bangladesh. The alarming increase in its frequency is a cause of concern. Violence against woman within South Asia includes rape and sexual abuse, trafficking, prostitution, domestic violence, dowry related deaths and psychological abuse. The reported case is of a 25 years old lady affected by acid burn in her face and adjoining part of the head during night while she was sleeping. On medicolegal point of view, the injury was homicidal in nature to run away without having a motive to kill the person. We should create public consciousness against this sort of brutal act. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.336-338